2007
DOI: 10.1063/1.2793507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ag content on the phase structure and piezoelectric properties of (K0.44−xNa0.52Li0.04Agx)(Nb0.91Ta0.05Sb0.04)O3 lead-free ceramics

Abstract: Articles you may be interested inInvestigation on transition behavior and electrical properties of (K0.5Na0.5)1-xLixNb0.84Ta0.1Sb0.06O3 around polymorphic phase transition region AIP Advances 4, 017125 (2014); 10.1063/1.4863200 Improved temperature stability of CaTiO 3 -modified [ ( K 0.5 Na 0.5 ) 0.96 Li 0.04 ] ( Nb 0.91 Sb 0.05 Ta 0.04 ) O 3 lead-free piezoelectric ceramics J. Appl. Phys.͑K 0.44−x Na 0.52 Li 0.04 Ag x ͒͑Nb 0.91 Ta 0.05 Sb 0.04 ͒O 3 lead-free piezoelectric ceramics were prepared by normal sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 26 publications
3
95
1
Order By: Relevance
“…These results indicate the (1 − x)KNLNS-xCT ceramics with x = 0.01 possess optimum piezoelectric properties at room temperature (d 33 ∼252 pC/N and k p ∼49%) [17]. Usually, the polymorphic phase transition (PPT) near or at room temperature is responsible for the improved piezoelectric properties of KNN-based ceramics [3,5,12]. However, the PPT of the (1 − x)KNLNS-xCT ceramics with x = 0.01 was shifted to below room temperature (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…These results indicate the (1 − x)KNLNS-xCT ceramics with x = 0.01 possess optimum piezoelectric properties at room temperature (d 33 ∼252 pC/N and k p ∼49%) [17]. Usually, the polymorphic phase transition (PPT) near or at room temperature is responsible for the improved piezoelectric properties of KNN-based ceramics [3,5,12]. However, the PPT of the (1 − x)KNLNS-xCT ceramics with x = 0.01 was shifted to below room temperature (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Considerable attention for lead-free piezoelectric ceramics was recently given to (K 0.50 Na 0.50 )NbO 3 (KNN)-based ceramics for their excellent piezoelectric properties, high Curie temperature and environmental friendliness [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The different additions are added into KNN to form new KNN-based ceramics for improving the densification and piezoelectric properties, such as KNN-LiSbO 3 [3], KNN-LiNbO 3 [6], KNN-LiNbO 3 -AgTaO 3 [8], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In this regard, several lead-free systems have emerged out including (Na 0.5 K 0.5 )NbO 3 (NKN), ZnO, (Bi 0.5 Na 0.5 )TiO 3 (BNT), and BaTiO 3 (BT) based compositions. 2,[6][7][8][9][10] Although the piezoelectric coefficient values of NKN and BNT systems have been improved using site engineering, [11][12][13] sintering aid 14 or a new synthesis technique; 2 their main drawbacks include the presence of highly volatile elements like Bi, Na, and K. This results in poor densification that leads to degradation in the physical properties.…”
mentioning
confidence: 99%
“…Effect of other ions such as Ag, Nb, Ta, Bi, Cu, Ca, etc. and combination two or three cations on KNN-LS ceramics were also studied by many authors [96][97][98][99][100][101][102][103][104][105][106][107][108] and promising results were reported. Wang et al reported that addition of Ag in KNN-LiTaO 3 ceramics increases the Curie temperature (T c = 438°C) and piezoelectric properties (d 33 = 252 pC/N) of the ceramic by normal sintering technique [109].…”
Section: Knbo 3 -Based Ceramicsmentioning
confidence: 99%